EFEKTIFITAS BIDANG PENDIDIKAN DASAR PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KAMPAR - Muhammad Amri; Mayarni Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Basic Education Sector at the Education and Culture Office of Kampar regency has the main duty to assist the head of the office in organizing curriculum and student activities, basic education and basic education infrastructure in the work environment of Kampar Education and Culture Office. The purpose of Basic Education in the Department of Education and Culture Kampar regency, the management of educational units at the level of primary school education, and First and Secondary Schools public and private equivalent so as to improve the quality of education and public access to adequate education services, Equitable, and affordable.The method used in this research is descriptive qualitative method, that is describing or explaining the existing problem by giving answer to the problem presented, referring to the theory concerned with the problem. The data collecting used in this research is interview, observation, and documentation study. Then, after all the information required in this study collected, then drawn conclusions.The results of the research show that for the achievement of the objectives in the Basic Education Sector, the strategy used only focuses on the mandate of duty which has been written in juridical. The process of analysis and policy formulation, and education needs planners have not involved educational units (schools) directly, or not yet integrated (integrated). Factors affecting the effectiveness of Basic Education Sector, including low coordination with education unit (school) is insidential (if needed), human resource capacity (employee) Basic Education Field which do not conduct study / scale priority of education requirement in unit Basic education, and inadequate facilities and technology thasana with the implementation of computerized system in the implementation of administrative service tasks.Keywords: Effectiveness, Organization, Educational Management, Basic Education